Impact of Digital Marketing Strategies on Consumer Purchasing Decisions in the Indonesian Market: The Mediating Role of Customer Satisfaction - Prananta, Arie Wahyu; Maulidiana, Lina; Sufa, Siska Armawati; Wahyudi, Muhammad Aria (IJBLE Scientific Publications Community Inc., 2024)
This research delves into the intricate dynamics of the Indonesian market, exploring the impact of digital marketing strategies on consumer purchasing decisions and the mediating role of customer satisfaction. Amidst a rapidly evolving digital landscape, characterized by increased internet penetration and a surge in online activities, businesses face the challenge of adapting their strategies to remain competitive. Leveraging a diverse and representative sample of 100 Indonesian respondents, this study employs a cross-sectional survey design and utilizes Partial Least Squares Structural Equation Modeling (PLS SEM) for data analysis. The findings reveal a significant positive relationship between digital marketing strategies and customer satisfaction, emphasizing the pivotal role of effective digital initiatives in shaping the overall consumer experience. Moreover, the study underscores the mediating influence of customer satisfaction on the relationship between digital marketing strategies and consumer purchasing decisions. These insights not only contribute to the academic discourse in marketing but also offer practical implications for businesses aiming to optimize their strategies in the dynamic Indonesian market.